MARKETING CONCEPT AS A TOOL FOR DEVELOPMENT OF TOURISM IN KOSOVO - UKAJ, Fatos (Journal of Environmental Management and Tourism, 2010)
Application of marketing in tourism, creates a clearer view into the actual state of development of tourism offers and the effects in tourism, especially emphasizing the elements of the marketing, such as promotion and distribution of tourist products The purpose of using marketing concept in tourisms activity is to stimulate and to help the development of tourism in Kosovo. Without successful functioning of marketing in today’s surrounds and world’s global business, tourism and the other business branches, would be convicted in failure. Although, the activity of tourism has a seasonal character, marketing concept with its tools will use advantages of the existing well-known tourism products, and then by its opportunities it will enable a better use of tourism capacities. With this given framework of research, marketing in tourism as one intensive economic activity within national tourism industry, has a distinct economic function in a country in which the Tourist product is being developed.